1996
DOI: 10.1159/000237284
|View full text |Cite
|
Sign up to set email alerts
|

In vivo lnterleukin-4 Regulation of Antibody Responses in Euthymic and Athymic Mice to a T-lndependent Antigen (Hydroxyethyl Starch)

Abstract: The aim of this work was to analyze the implication of IL-4 in the antibody response induced in vivo after immunization with a class II T-cell-independent (TI) antigen. IL-4 suppression, through administration of a rat monoclonal antibody antimurine IL-4 (11B11), in euthymic BALB/c mice during the course of immunization with the DNP-coupled hydroxyethyl starch (TI antigen), inhibited the production of anti-DNP IgG1 antibodies, potentiated the synthesis of IgG2a and had no effect on other isotypes (IgM, IgG2b a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Our results are in agreement with the observation of an IL-4 regulation of in vivo antibody production in response to TI-2 antigens in experimental animals (11). Th1 cells do not appear to be involved in the response to pneumococcal polysaccharides, since neither IL-12 nor IFN-␥ mRNA increased in our experiments.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with the observation of an IL-4 regulation of in vivo antibody production in response to TI-2 antigens in experimental animals (11). Th1 cells do not appear to be involved in the response to pneumococcal polysaccharides, since neither IL-12 nor IFN-␥ mRNA increased in our experiments.…”
Section: Discussionsupporting
confidence: 93%
“…TI antigens have been subdivided into type 1 (TI-1) antigens, which have no T-cell interaction, and type 2 (TI-2) antigens, which have some interaction with T cells. Recent studies have shown that pneumococcal polysaccharides are TI-2 antigens, which stimulate T-cell help in regulating antibody production (11,14,20,21,31). However, neither the way in which such stimulation occurs nor the regulatory mechanism of antibody production is well understood.…”
mentioning
confidence: 99%
“…Ovalbumin (OVA) five times crystallized and keyhole limpet hemocyanin (KLH) were obtained from Calbiochem (La Jolla, CA, USA). DNP‐OVA and DNP‐hydroxyethylstarch (DNP‐HES), thymus‐dependent and thymus‐independent antigens, respectively, were prepared, as previously described 22 23 .…”
Section: Methodsmentioning
confidence: 99%
“…DNP-OVA and DNP-hydroxyethylstarch (DNP-HES), thymusdependent and thymus-independent antigens, respectively, were prepared, as previously described. 22 A. suum worm extract (ASC) was prepared as described by Strejan and Campbell. 23 The protein component from A. suum adult worm extract, PAS-1, was purified by affinity chromatography using the mAb MAIP-1 coupled to Sepharose 4B, as previously described.…”
Section: Antigensmentioning
confidence: 99%